Pengaruh Transfer Pricing , Thin Capitalization, Dan Political Connection Terhadap Tingkat Agresivitas Pajak (Studi Empiris Pada Perusahaan Sektor Energi yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2024) - Ika Rizkiyani; Erliana Erliana; Linawati Linawati (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to: 1) Examine and analyze the effect of Transfer Pricing on tax aggressiveness, 2) Analyze the effect of Thin Capitalization on tax aggressiveness, 3) Evaluate the effect of Political Connection on tax aggressiveness, and 4) Assess the simultaneous effect of Transfer Pricing , Thin Capitalization, and Political Connection on tax aggressiveness in energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. This research uses a quantitative approach with panel data regression using the Fixed Effect Model (FEM) and purposive sampling technique, with a total of 100 observations from annual financial reports of energy companies. The results show that: 1) Transfer Pricing has a significant effect on tax aggressiveness (p=0.0370), 2) Thin Capitalization also has a significant effect on tax aggressiveness (p=0.0007), 3) Political Connection does not have a significant effect on tax aggressiveness (p=0.4048), and 4) simultaneously, the three independent variables have a significant effect on tax aggressiveness (F-statistic = 15.416 (p=0.0000). The Adjusted R² value of 0.762 indicates that the model is able to explain 76.2% of the variation in tax aggressiveness, indicating a strong explanatory power of the model based on the variables included. Furthermore, the normality test results show that the residuals are normally distributed, as indicated by the Jarque-Bera value of 1.594 with a probability of 0.4506 (> 0.05).